Vehicle brand perception among generation X in the South African higher education sector - Mhlongo, Bright; Msosa, Steven Kayambazinthu (Management and Entrepreneurship: Trends of Development, 2023)
This study sought to ascertain the general perceptions regarding the significance attributed to various passenger motor vehicle brands among Generation X, a demographic group that constitutes most car purchasers. The research was carried out in the province of KwaZulu-Natal, where data was gathered from four higher education institutions. A study was conducted utilising a quantitative, descriptive, and cross-sectional research design. The survey method was employed to collect data from a sample of 400 individuals affiliated with a university as either staff or students belonging to the Generation X cohort. The data was analysed using descriptive statistics by means of the SPSS version 23. The research examined distinct brand dimensions, specifically focusing on factors associated with quality, value, personal and group identity, status, and family traditions. The results of this study indicate that a significant proportion of the participants expressed agreement with the notion that their selection of a vehicle brand was influenced by factors such as perceived quality, value, individual and collective identity, social status, and family traditions This study could provide valuable insights to scholars, professionals in the industry, and motor vehicle brand manufacturers, enabling them to develop a comprehensive comprehension of the challenges faced within the industry, academia, and consumer domain pertaining to the perceptions surrounding various motor vehicle brands. Moreover, the results of this research can serve as a valuable tool for identifying a more suitable marketing approach to enhance consumer attitudes towards automotive brands.JEL Classification: D21, D23.